2014
DOI: 10.4028/www.scientific.net/amm.538.179
|View full text |Cite
|
Sign up to set email alerts
|

Research on Linear Motor in Deep Exploration Based on Experiment

Abstract: Linear motor is applied in the seismic source system of deep well seismic wave exploration, which belongs to international cutting-edge techniques of the exploration industry. Compared to traditional blasting techniques, the technique has better safety performance and lower cost. It is concluded that the setting basic frequency is a critical factor for start-up force of the linear motor in the seismic source system based on the experiment and relative data. The concept of practical efficiency is proposed. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…The source system, linear motor access to the primary winding of symmetrical three phase current, it will generate an axial moving magnetic field inside the motor, the magnetic field cutting secondary conductive surface induction electric potential and induced current, current carrying conductor in the mobile magnetic field again by the effect of electromagnetic force, so that the secondary hammer rod to move below the linear velocity of the magnetic field from the hammer anvil block up to the top of the device; And then secondary hammer rod drop hammer on the anvil block produce seismic waves, while receive control vehicles in the near distance receives a signal, by the computer for data collection, analysis and processing, thus it is concluded that the relevant results [1] .…”
Section: Experiments Principlementioning
confidence: 99%
“…The source system, linear motor access to the primary winding of symmetrical three phase current, it will generate an axial moving magnetic field inside the motor, the magnetic field cutting secondary conductive surface induction electric potential and induced current, current carrying conductor in the mobile magnetic field again by the effect of electromagnetic force, so that the secondary hammer rod to move below the linear velocity of the magnetic field from the hammer anvil block up to the top of the device; And then secondary hammer rod drop hammer on the anvil block produce seismic waves, while receive control vehicles in the near distance receives a signal, by the computer for data collection, analysis and processing, thus it is concluded that the relevant results [1] .…”
Section: Experiments Principlementioning
confidence: 99%